Association of ERCC1 SNPs with outcome in platinum-treated patients with advanced urothelial cancer: A Hellenic Cooperative Oncology Group study - Nikitas, N.; Karadimou, A.; Tsitoura, E.; Soupos, N.; Tsiatas, M.; Karavasilis, V.; Pectasides, D.; N. Pavlidis; Chrisofos, M.; Adamakis, I.; Murray, S.; Fountzilas, G.; et al. (Pharmacogenomics, 2012)
Aim: The association between two polymorphisms of ERCC1 and treatment outcomes after platinum-based chemotherapy in patients with advanced urothelial cancer (UC) was examined. Materials & methods: Genotyping of 19007C>T and 8092C>A polymorphisms was determined by PCR amplification and RFLP in 113 advanced UC patients, treated with platinum-based chemotherapy. Results: Seventy eight patients (69%) were carriers of the 19007T polymorphic allele: 51 (45%) heterozygotes and 27 (24%) homozygotes. Fifty three (47%) patients were carriers of the 8092A polymorphic allele: the frequencies of C/A and A/A genotypes were 37% and 10%, respectively. The T/T genotype was independently associated with prolonged median cancer-specific survival (not-reached vs 14.8 months; p = 0.026). There was no interaction between T/T or any other genotype with the type of platinum derivative (cisplatin/carboplatin). Conclusion: 19007C>T, especially in its homozygotic state, but not 8092C>A polymorphism, could be a useful prognostic marker in advanced UC treated with platinum-based chemotherapy. Original submitted 17 July 2012; Revision submitted 21 September 201. © 2012 Future Medicine Ltd.
Keywords: Cisplatin; human ERCC1 gene; nucleotide excision repair; single-nucleotide polymorphism; urothelial cancer